INTERCULTURAL CITIZENSHIP IN THE EFL CLASSROOM: A SURVEY ON KAZAKHSTANI TEACHERS’ AND STUDENTS’ PERCEPTIONS - Gerfanova, Elmira; Rudik, Zarina (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Over the past decade, the relevance of intercultural citizenship (IC) education has intensified due to increasing global interactions, internationalization, and the participation of teachers and students in a global network. This education aims at cultivating individuals who demonstrate an active civic stance, both locally and globally, and possess knowledge and skills crucial for functioning in the context of linguistic and cultural diversity. The study aims to investigate how EFL teachers and students perceive the concept of intercultural citizenship. The participants for this study were 23 EFL teachers and 47 students from two universities in Kazakhstan. The primary method of data collection was a structured questionnaire containing open-ended items that asked the participants to express their thoughts and opinions on the qualities, responsibilities, and duties they believe are essential for an intercultural citizen. The obtained data revealed similarities between teachers’ and students’ perceptions of IC: both teachers and students highlight the importance of cultural awareness, empathy and intercultural communication skills. At the same time, the findings indicate that EFL teachers and students have a limited understanding of the concept of intercultural citizenship. The results of the study may provide insights for educators and curriculum developers into EFL teachers’ and students’ perceptions of intercultural citizenship, which may help to develop effective strategies and approaches to integrating the IC component into the EFL classroom.